(untitled) (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Many different techniques of reduction of acute anterior shoulder dislocation have been described. The aim of this study was to evaluate the effectiveness of external rotation method for reduction of acute anterior shoulder dislocation. Methods: Fifty-one patients with acute anterior shoulder dislocations with or without greater tuberosity fracture were reduced during a period from January 2013 to January 2015. The external rotation method was used as an initial reduction method performed by orthopaedic surgeon on call or residents. Data sheets completed by the orthopaedic surgeon on call or residents were evaluated with regard to the type of dislocation, the effectiveness of the procedure in achieving reduction, the need for premedication, the ease of performing the reduction, and complications, if any. Results: There were 42 male and nine female patients between 18 to 78 years. Among 51 patients, 49 had successful reduction. No premedication was required in 33 patients who had a successful reduction, and the average time required for reduction in 23 patients was within two minutes whereas 20 patients reduced within five minutes. Only four patients reported severe pain during the process of reduction. The method was not successful in two patients with subcoracoid dislocation associated with displaced fracture of the greater tuberosity. Conclusions: External rotation method is reliable, safe, simple and relatively painless method for reduction of acute anterior shoulder dislocation.